Economic viability and environmental sustainability of a grid-connected solar PV plant in Yaounde - Cameroon using RETScreen expert. Issue 1 (31st December 2023) - Iweh, Chu Donatus; Gyamfi, Samuel; Tanyi, Emmanuel; Effah-Donyina, Eric
Abstract: The Cameroon power sector is currently undergoing a period of transition with government setting ambitions to increase the generation of clean electricity to meet the rapidly growing demand. A significant aspect of this transition is the phasing out of some thermal plants and supporting power generation with renewables. This can be achieved through the heavy exploitation of the renewable energy resources in the country. In line with this goal, the study assesses the feasibility of a 211.75 MW solar PV power plant in Yaounde, Cameroon using RETScreen Expert. The simulation showed an annual electricity production of 304, 668.191 MWh with arrays mounted on a fixed axis. The model considered a debt ratio of 40%, debt interest rate of 12%, PV cost per kW of 1371 and a total system initial cost of 291, 791, 500. The annual revenue from exporting power to the grid was 36, 560, 183 and a capacity factor of 16.4%. The solar PV project was economically viable with a cost of energy (COE) of 75.43/MWh or 0.075/kWh and a gross annual GHG emission reduction potential of 61, 004.5 tCO2 corresponding to 141, 870.9 barrels of crude oil not used throughout the project life time. The benefit-cost ratio obtained in the simulation was 4.5 which implies that the project is profitable (ratio is greater than 1). The project break-even point of equity payback was 9.2 years while the simple payback was 8.9 years. The PV system had an IRR-assets of 7.4%, which was below the debt interest rate of Cameroonian financial institutions hence, the project will be attractive to investors. Also, the project risk and sensitivity analysis showed that a reduction in the project's initial cost had a significant effect on the net present value (NPV) and the cost of energy production. Similarly, a rise in the grid electricity export reduced the cost of energy production when the confidence level was set to 90%.